2023
DOI: 10.38007/wppcp.2023.040102
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Method of River Water Pollution Prevention and Early Warning System Supporting Spectrum Classification and 3D Remote Sensing Technology

Abstract: In recent years, people around the world are living in better and better conditions, and people are demanding more and more from their environment, and pollution of the water environment has become the most serious environmental hazard. In many areas, due to the strong development of agriculture and industry, their pollutants are discharged directly into nearby river basins, leading to eutrophication of water bodies. Failure to carry out river water pollution (WP) prevention and control not only poses a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…As can be seen from the experiments of the two groups, this content is based on the objective situation, and there is no relevant particularity. Both fast and slow performance in mutual verification can be positioned according to this fusion system [21]. According to the above experimental results, it can be concluded that the system can achieve a more accurate positioning effect in motion after using "5G + Beidou" and 3D point cloud image fusion.…”
Section: R E T R a C T E D A R T I C L E 5 Experimental Verification ...mentioning
confidence: 76%
“…As can be seen from the experiments of the two groups, this content is based on the objective situation, and there is no relevant particularity. Both fast and slow performance in mutual verification can be positioned according to this fusion system [21]. According to the above experimental results, it can be concluded that the system can achieve a more accurate positioning effect in motion after using "5G + Beidou" and 3D point cloud image fusion.…”
Section: R E T R a C T E D A R T I C L E 5 Experimental Verification ...mentioning
confidence: 76%